2017
DOI: 10.1177/1708538117727360
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and quality of life after ruptured abdominal aortic aneurysm repair

Abstract: Objectives To evaluate long-term outcome and quality of life after open and endovascular repair of ruptured abdominal aortic aneurysms. Methods All consecutive ruptured abdominal aortic aneurysm patients at the St. Antonius Hospital treated for ruptured abdominal aortic aneurysm between January 2005 and January 2015 were included. Mortality, morbidity, and re-interventions within 30 days and during follow-up were registered. Quality of life was measured with Short Form-36 questionnaire among survivors. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Patients who underwent an aorto-aortic bypass tended to have higher scores than those who underwent an aorto-bi-iliac or bifemoral bypass, regardless of the age of the individuals. This finding is consistent with several previous studies that showed that, in the long term (more than one year after the intervention), patients who undergo surgery using the EVAR technique have a lower score on the Physical Function dimension and on the scales of the Summary Component, than patients who undergo OR [ 13 , 23 , 24 , 25 ]. The EVAR technique is usually indicated in patients with high surgical risk, but is associated with a high incidence of reoperations and long-term complications [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients who underwent an aorto-aortic bypass tended to have higher scores than those who underwent an aorto-bi-iliac or bifemoral bypass, regardless of the age of the individuals. This finding is consistent with several previous studies that showed that, in the long term (more than one year after the intervention), patients who undergo surgery using the EVAR technique have a lower score on the Physical Function dimension and on the scales of the Summary Component, than patients who undergo OR [ 13 , 23 , 24 , 25 ]. The EVAR technique is usually indicated in patients with high surgical risk, but is associated with a high incidence of reoperations and long-term complications [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, few studies have analysed the long-term results of the SF-36 questionnaire in AAAs. Reported data indicate a progressive decrease in all the parameters of the SF-36 questionnaire, particularly those that reflect physical activity, as the age of the patients increases [ 13 , 14 , 15 , 16 ]. In addition, some publications have reported that patients treated by EVAR show a more marked decrease than OR patients [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information in the literature is not available on QoL in octogenarians after rAAA repair, but a few studies have reported on QoL after rAAA in the general population. 25e27 Tambyraja et al 23 and Yildirim et al 27 mentioned that survivors of rAAA have similar long term QoL scores to the age matched population. The IMPROVE trial (Immediate Management of the Patient with Ruptured Aneurysm) compared QoL between patients who underwent OR and EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal aortic aneurysm (AAA) is a vascular wall degenerative disease characterized by immune response, degradation of extracellular matrix, apoptosis of vascular smooth muscle cell and oxidative stress, because the growth and rupture of the aneurysm was uncertained that makes it high potentially lethal [1] . At present, surgical treatment of AAA only includes open surgical repair (OSR) and endovascular aneurysm repair (EVAR), the survival rate of patients treated with AAA is low and most of them would choose to undergo acute AAA repair again [2]. Small aneurysms and AAA in the early stage have no clinical symptoms and can't be treated by surgery, and there are still no effective therapy targets to intervene the evolution of AAA [3].…”
Section: Introductionmentioning
confidence: 99%